Nitrogen removal by algal-bacterial consortium during mainstream wastewater treatment: transformation mechanisms and potential N₂O mitigation - Li, Qi (2023)
This work investigated nitrogen transformation pathways of the algal-bacterial consortium as well as its potential in reducing nitrous oxide (N2O) emission in enclosed, open and aerated reactors. The results confirmed the superior ammonium removal performance of the algal-bacterial consortium relative to the single algae (Chlorella vulgaris) or the activated sludge, achieving the highest efficiency at 100% and the highest rate of 7.34 mg N g MLSS-1 h-1 in the open reactor with glucose. Enhanced total nitrogen (TN) removal (to 74.6%) by the algal-bacterial consortium was achieved via mixotrophic algal assimilation and bacterial denitrification under oxygen-limited and glucose-sufficient conditions. Nitrogen distribution indicated that ammonia oxidation (∼41.8%) and algal assimilation (∼43.5%) were the main pathways to remove ammonium by the algal-bacterial consortium. TN removal by the algal-bacterial consortium was primarily achieved by algal assimilation (28.1-40.8%), followed by bacterial denitrification (2.9-26.5%). Furthermore, the algal-bacterial consortium contributed to N2O mitigation compared with the activated sludge, reducing N2O production by 35.5-55.0% via autotrophic pathways and by 81.0-93.6% via mixotrophic pathways. Nitrogen assimilation by algae was boosted with the addition of glucose and thus largely restrained N2O production from nitrification and denitrification. The synergism between algae and bacteria was also conducive to an enhanced N2O reduction by denitrification and reduced direct/indirect carbon emissions.